Measuring local government technical (in)efficiency: An application and comparison of FDH, DEA and econometric approaches - Benny Geys; Wim Moesen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Economic efficiency – understood in terms of jurisdictions providing a maximum amount of output for a given level of inputs – is one potential means to evaluate public policies. Various approaches, however, co-exist to measure the (technical) efficiency of organizations. Given that these rely on different underlying assumptions, it is important to assess whether, and to what extent, the approach taken affects the outcome of efficiency studies. The present paper employs a dataset of local governments in Flanders in 2000 to compare the three common approaches to measure (in)efficiency (i.c. FDH, DEA and econometric techniques). Our results indicate that the methodological choices of instrumentation have a substantial effect on analytic performance measurement. Hence, assessing the robustness of the results across various approaches to efficiency measurement is crucial to avoid incorrect inferences. – – Ökonomische Effizienz – verstanden im Sinne der Maximierung der Ausbringungsmenge für ein gegebenes Inputlevel – ist ein gängiges Mittel um staatliche Politiken zu evaluieren. Allerdings existieren mehrere Herangehensweisen, um die (technische) Effizienz von Organisationen zu messen. Unter der Voraussetzung, dass diese auf unterschiedlichen Annahmen basieren, ist es von Interesse, ob und inwiefern die gewählte Methode die Ergebnisse einer Untersuchung beeinflusst. Mit dem Datenmaterial aus flämischen Gemeindeverwaltungen im Jahr 2000 vergleichen wir die drei bedeutendsten Methoden der (In-)Effizienzmessung (FDH, DEH und ökonometrische Verfahren). Unsere Ergebnisse zeigen, dass die Wahl der Methode einen substantiellen Einfluss auf die Performancemessung hat. Aus diesem Grunde erscheint es mitunter unerlässlich, die Robustheit von Ergebnissen anhand verschiedener Effizienzmethoden zu überprüfen, um nicht Gefahr zu laufen, unzulässige Folgerungen zu ziehen.
Keywords: 330; free disposal hull; data envelopment analysis; stochastic frontiers; government (in)efficiency; Flemish municipalities; Kommunalverwaltung; Kommunale Dienstleistung; Performance-Messung; Data-Envelopment-Analyse; Belgien